Efectos de la estimulación magnética transcraneal aplicada en pacientes con Parkinson. - Hernández Palaguachi, Josué David (2025)
Parkinson's Disease (PD) is a progressive neurodegenerative disorder linked to aging, characterized by the loss of dopaminergic neurons in the black substance compact and the accumulation of Lewy bodies. This leads to motor symptoms such as bradykinesia, rigidity, and resting tremor, as well as non-motor symptoms like depression and anxiety. This research aims to synthesize existing scientific evidence on physiotherapeutic interventions using transcranial magnetic stimulation (TMS) in Parkinson's patients. It identifies their effectiveness and reported outcomes to contribute insights into clinical benefits and contraindications. A literature review was conducted using a documentary approach to achieve this objective, leveraging recognized databases such as PubMed, SciELO, and Science Direct. Twenty randomized clinical trials were selected to provide high-quality data, with studies evaluated using the PEDro scale. While physiotherapy complements therapeutic approaches through various techniques in PD treatment, transcranial magnetic stimulation (TMS) has emerged as a non-invasive therapy. Current protocols demonstrate improvements in motor and non-motor symptoms, showing positive and clinically relevant outcomes for PD patients.